Avaliação de genótipos de batata-doce na região de Areia-PB - Guimarães, Luciana Menino (2016)
In the Brazilian’s northeastern region, the sweet potato is cultivated for small farmers in the familiar agriculture system, consisting in an alternative of feeding and generation of employment and income. We aimed with this work to evaluate the production and the behavior of genotypes of sweet potato in the region of Areia, PB. The work was carried out at the Universidade Federal da Paraíba, in Areia-PB, using randomized block experimental design with six treatments and four replicates. The treatments were represented by the genotypes Rainha Branca, Melindrosa, Jardim, Campina, Paraíba and Jardim Vitaminada. The characteristics green matter and dry matter plant-1 , leaf area, mean root matter, number and production of commercial roots-1 and total, as well as commercial productivity of roots were evaluated. Data were submitted to analysis of variance, were realized mean tests and later were realized correlation of Pearson. We also realized simple correlation among the productivity of commercial roots and the other characteristics. The genotype Rainha Branca presented higher value for green matter plant-1 (17.50 kg). The production of dry matter plant 1 was higher in the genotypes Rainha Branca and Paraíba, respectively, 137.75 and 131.75 g. The highest values for leaf area were verified in the genotypes Jardim and Rainha Branca. The genotype Rainha Branca was it that produced commercial roots with higher mean matter, 224.7 g. The number of commercial roots was upper in the genotype Jardim Vitaminada. The higher production of commercial roots plant-1 was verified in the genotype Paraíba. The higher total productivities of roots were reached in the genotypes Melindrosa and Paraíba, respectively 35.5 and 37.5 t ha-1 , while elevated productivities of commercial roots were obtained in the genotypes Melindrosa, Paraíba and Jardim Vitaminada, 23.2, 24.0 and 24.2 t ha-1 , respectively. There were significant positive correlation among productivity of commercial roots with the number and production of commercial roots plant-1 and the total productivity of roots.